Influence of Customer Relationship Management on Customers’ Retention in the Insurance Industry in Accra, Ghana - Ofosu-Boateng, Ibrahim (British Journal of Marketing Studies, 2020)
The study examines the influence of customer relationship management on customers’ retention in the insurance industry in Accra, Ghana. The objective of the study was to examine the relationship between customer relationship management and customers’ satisfaction in the insurance industry in Accra, Ghana; to determine the relationship between customer relationship management and customers’ retention in the insurance industry in Accra, Ghana and; to identify the challenges obstructing customer relationship management’s strategies in the insurance industry in Accra, Ghana. Convenience sampling technique was used to gather data form a sample of 200 customers of insurance firms in Accra, Ghana, using structured interview guide and data analyses carried out using SPSS version 20. The findings of the study showed a direct effect of customer relationship management on customers’ satisfaction. Also, the study revealed a significant positive relationship between customer relationship management and customers’ retention. Based on these findings, the study recommends that the insurance industry in Accra, Ghana, should continue to deliver excellent customer service to customers in order to keep satisfying them. This can be achieved by understanding their expectations and meeting them. More so, the study recommends insurance firms in Accra, Ghana, to continue to deliver value laden-relationships with customers in order to keep retaining them since retention is key in any given competitive business environment.